New Fathers' Perinatal Depression and Anxiety—Treatment Options: An Integrative Review. (July 2017) - O'Brien, Anthony P.; McNeil, Karen A.; Fletcher, Richard; Conrad, Agatha; Wilson, Amanda J.; Jones, Donovan; Chan, Sally W.
More than 10% of fathers experience depression and anxiety during the perinatal period, but paternal perinatal depression (PPND) and anxiety have received less attention than maternal perinatal mental health problems. Few mainstream treatment options are available for men with PPND and anxiety. The aim of this literature review was to summarize the current understanding of PPND and the treatment programs specifically designed for fathers with perinatal depression. Eight electronic databases were searched using a predefined strategy, and reference lists were also hand searched. PPND and anxiety were identified to have a negative impact on family relationships, as well as the health of mothers and children. Evidence suggests a lack of support and tailored treatment options for men having trouble adjusting to the transition to fatherhood. Of the limited options available, cognitive behavioral therapy, group work, and blended delivery programs, including e-support approaches appear to be most effective in helping fathers with perinatal depression and anxiety. The review findings have important implications for the understanding of PPND and anxiety. Future research is needed to address the adoption of father-inclusive and father-specific models of care to encourage fathers' help-seeking behavior. Inclusion of male-specific requirements into support and treatment options can improve the ability of services to engage new fathers. Psychotherapeutic intervention could assist to address the cognitive differences and dissonance for men adjusting to the role of father, including male identity and role expectations.